An Investigation of Teacher-Student Relationship in Islamic History of Education - Zulqarnain, Muhammad (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract This paper is an attempt to explore the nature of the relationship between teachers and students in Islamic history of education. The research was triggered as a result of investigation that highlighted disappointing teacher-student relationship in contemporary education system. By employing descriptive and qualitative research method the study established that teacher-student relationship had been given an astonishing milieu in Islamic history and was considered one of the core causes for education par excellence. This relationship was based on care, sympathy, mutual understanding, cooperation and common respect. It was concluded that this healthy relationship enhanced class participation, confidence, critical thinking, research and oral communication skills including in areas of interpersonal skills and personality development of the students. The research, therefore, recommends establishing healthy relationship among students and teachers by captivating direction from Islamic history of education since it is perceived not only to improve quality of education but also to equip learners with additional competencies.   Abstrak Artikel ini adalah sebuah percobaan untuk meneliti hakikat hubungan antara guru dan siswa dalam sejarah pendidikan Islam. Penelitian dipicu sebagai hasil dari investigasi yang mengarisbawahi hubungan buruk antara guru dan siswa dalam sistem pendidikan yang kontemporer. Dengan menggunakan metode penelitian deskriptif dan qualitatif, studi membentuk bahwa hubungan guru-siswa sudah diberikan lingkungan pergaulan yang mengherankan dalam sejarah Islam dan dianggap salah satu akar penyebab persamaan mutu pendidikan. Hubungan ini terbangun atas dasar perhatian, simpati, saling memahami, kerjasama dan menghormati. Hal tersebut disimpulkan bahwa hubungan yang sehat ini meningkatkan partisipasi kelas, kepercayadirian, berpikir kritis, penelitian dan kemampuan komunikasi secara lisan termasuk dalam ranah kemampuan interpersonal dan pengembangan diri siswa. Oleh karena itu, penelitian ini merekomendasikan untuk membangun hubungan yang sehat antara siswa dan guru dengan mengarahkan arahan dari sejarah pendidikan Islam karena dianggap tidak hanya untuk meningkatkan kualitas pendidikan, tetapi juga untuk membekali siswa dengan kompetensi tambahan.   How to Cite : Zulqarnain, M. (2017). An Investigation of Teacher-Student Relationship in Islamic History of Education. TARBIYA: Journal of Education in Muslim Society, 4(1), 13-21. doi:10.15408/tjems.v4i1. 5317. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5317